Power, supply chain integration and quality performance of agricultural products: evidence from contract farming in China. Issue 13 (3rd October 2021) - Fu, Shaoling; Zhan, Yuanzhu; Ouyang, Jun; Ding, Yalan; Tan, Kim Hua; Fu, Lingmei
Abstract: Improving the quality of agricultural products is crucial for facilitating sustainable agricultural development. One widely embraced approach is contract farming, which generates guarantees—necessary for sustaining the continuous operations of vulnerable farmers—while enabling manufacturers to manage the aggregate supply chain risks and prices. Although management researchers have investigated power and quality performance issues between organisations, few have examined their impact on contract farming. This paper extends the literature by examining the relationships between power, supply chain integration and the quality performance of agricultural products, from the perspectives of farm households and agribusiness companies in contract farming. This study proposes and empirically examines a model, applying survey data from 78 agricultural companies and 321 peasant householders in China. The results show that different types of power have different effects on contract farming. In particular, non-economic power significantly and positively affects supply chain integration. Its impact on process coordination is greater than its impact on information sharing. The effect of economic power on supply chain integration is different from the binary perspective. These findings have positive theoretical and practical significance for agribusiness and will help farmers to improve the quality of primary agricultural products and achieve sustainable agricultural development.